The book of the twelve: a Pentecostal commentary - Thomas, John Christopher (Pentecostal commentary series, 2020)
This commentary, written from a distinctively Pentecostal perspective is primarily for pastors, lay persons and Bible students. It is based upon the best scholarship, written in popular language, and communicates the meaning of the text with minimal technical distractions. The authors offer a running exposition on the text and extended comments on matters of special significance for Pentecostals. They acknowledge and interact with alternative interpretations of individual passages, and this commentary also provides periodic opportunities for reflection upon and personal response to the biblical text